Mutations of hMLH1 gene and sporadic breast cancer - Bryś, Magdalena; Małgorzata Krajewska, Wanda; Zych, Aneta; Kulig, Andrzej; Romanowicz-Makowska, Hanna (Menopause Review/Przegląd Menopauzalny, 2004)
Purpose: In order to test the hypothesis that the hMLH1 gene is compromised in the initiation and progression of breast cancer, we have investigated mutations of exon 8 and 14 using PCR-SSCP technique. Material and methods: Paraffin-embedded tumour and peripheral venous blood of 35 patients with breast ductal carcinoma were studied. The single strand conformational polymorphism (SSCP) analysis of the hMLH1 gene was performed by polymerase chain reaction (PCR). PCR primers were prepared to amplify the full sequence of exons 8 and 14, and exon-intron borders. Samples with identified hMLH1 mutations were sequenced using ABI Ready Reaction Dye Terminator Cycle Sequencing kit and the ABI Prism 377 sequencer. Results and conclusions: hMLH1 gene mutations were found in 3/35 (8%) studied cases of breast cancer. They were identified in exon 8. No mutations were detected in exon 14. Two sequence variants were identified in hMLH1 gene. One, a ATC→GTC substitution in codon 219 (exon 8) changing isoleucine to valine. The other mutation detected in hMLH1 was a CGA→TGA substitution in codon 226 (exon 8), creating a stop codon, predicted to generate a truncated protein. hMLH1 gene defects involving exon 8 and 14 are extremely rare events and thus seems not to be involved in sporadic breast cancer.